Pseudocarcinomatous hyperplasia of the fallopian tube mimicking a tubal neoplasm: A rare entity - Gireesha Rawal; Sufian Zaheer; Amit Kumar Yadav; Indrani Dhawan (Wolters Kluwer Medknow Publications, 2018)
Pseudocarcinomatous hyperplasia of the fallopian tube is a rare, reactive response to an underlying inflammatory or neoplastic process. Only a few cases have been reported in literature. It is a benign condition that mimics a malignant neoplasm clinically and radiologically. Thus, a preoperative diagnosis of this entity is important to avoid radical surgical treatment. We report a case of pseudocarcinomatous hyperplasia of the fallopian tube in a 27-year-old female, which was clinically and radiologically thought to be a tubal neoplasm. The approach to such a case and the differentiating features from adenocarcinoma have also been discussed.